Clinical impact of exome sequencing in the setting of a general pediatric ward for hospitalized children with suspected genetic disorders - Kagan, Maayan; Semo-Oz, Rotem; Ben Moshe, Yishay; Atias-Varon, Danit; Tirosh, Irit; Stern-Zimmer, Michal; Eliyahu, Aviva; Raas-Rothschild, Annick; Bivas, Maayan; Shlomovitz, Omer; Chorin, Odelia; Rock, Rachel; et al. (Frontiers in Genetics, 2023)
Background: Genetic conditions contribute a significant portion of disease etiologies in children admitted to general pediatric wards worldwide. While exome sequencing (ES) has improved clinical diagnosis and management over a variety of pediatric subspecialties, it is not yet routinely used by general pediatric hospitalists. We aim to investigate the impact of ES in sequencing-naive children suspected of having monogenic disorders while receiving inpatient care. Methods: We prospectively employed ES in children admitted to the general pediatric inpatient service at a large tertiary medical center in Israel. Genetic analysis was triggered by general and/or subspecialist pediatricians who were part of the primary inpatient team. We determined the diagnostic yield among children who were referred for ES and observed the effects of genetic diagnosis on medical care. Results: A total of fifty probands were evaluated and exome sequenced during the study period. The most common phenotypes included were neurodevelopmental (56%), gastrointestinal (34%), and congenital cardiac anomalies (24%). A molecular diagnosis was reached in 38% of patients. Among seven patients (37%) the molecular genetic diagnosis influenced subsequent clinical management already during admission or shortly following discharge. Conclusions: We identified a significant fraction of genetic etiologies among undiagnosed children admitted to the general pediatric ward. Our results support that early application of ES may be maximized by pediatric hospitalists' high index of suspicion for an underlying genetic etiology, prompting an in-house genetic evaluation. This framework should include a multidisciplinary co-management approach of the primary care team working alongside with subspecialties, geneticists and bioinformaticians.